Silver ion-doped CdTe quantum dots as fluorescent probe for Hg2+ detection. Issue 64 (23rd October 2020) - Li, Huazheng; Lu, Wangwei; Zhao, Gaoling; Song, Bin; Zhou, Jing; Dong, Weixia; Han, Gaorong
Abstract : Ag-doped CdTe QDs emit multiple-fluorescence peaks, and the relationship between fluorescence intensity and the concentration of Hg 2+ is established. Two linear relationships are obtained, which is benefit to the extension of detection range. Abstract : Mercury(ii ), which is a well-known toxic species, exists in the industrial waste water in many cases. In the present work, CdTe quantum dots (QDs) are studied as a fluorescence probe for Hg 2+ detection. Ag ions are induced to QDs to enlarge their detection concentration range. l -cysteine is employed in the QD-based fluorescence probe to connect QDs with Hg 2+ . X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy results indicate the formation of zinc blende CdTe QDs with sizes of ∼5 nm and the existence of Ag + in crystalline CdTe. Photoluminescence (PL) spectra and PL decay spectra were acquired to investigate the emission mechanism of Ag-doped CdTe QDs, revealing multi-emission in QD samples with higher concentrations of Ag + doping. The highest PL quantum yield of the QD samples was 59.4%. Furthermore, the relationship between the fluorescence intensity and the concentration of Hg 2+ has been established. Two linear relationships were obtained for the plot of F/F0 against Hg 2+ concentration, enlarging the detection concentration range of Hg 2+ .